2001
DOI: 10.1161/hc3001.092037
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Analysis of Local Delivery of Paclitaxel Via a Polymer-Coated Stent

Abstract: Background-Paclitaxel can inhibit vascular smooth muscle proliferation in vitro, and early studies suggest that paclitaxel may be useful in preventing restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
225
1
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 368 publications
(248 citation statements)
references
References 23 publications
14
225
1
6
Order By: Relevance
“…A small one-year study and subsequent large clinical trial with sirolimus reported a dramatic reduction of restenosis. 7,8 Although preclinical animal studies with either of these agents have demonstrated efficacy at 28 days, long-term studies show inconsistent results [2][3][4]9 (and Andrew J. Carter, MD, Providence Heart Institute, Providence, Ore, unpublished data, 2002; Alan W. Heldman, MD, Johns Hopkins University, Baltimore, Md, unpublished data, 2002). In humans, healing of a bare stainless steel stent usually takes between 3 and 6 months, whereas in animals this response is usually complete by 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A small one-year study and subsequent large clinical trial with sirolimus reported a dramatic reduction of restenosis. 7,8 Although preclinical animal studies with either of these agents have demonstrated efficacy at 28 days, long-term studies show inconsistent results [2][3][4]9 (and Andrew J. Carter, MD, Providence Heart Institute, Providence, Ore, unpublished data, 2002; Alan W. Heldman, MD, Johns Hopkins University, Baltimore, Md, unpublished data, 2002). In humans, healing of a bare stainless steel stent usually takes between 3 and 6 months, whereas in animals this response is usually complete by 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…3 The stented iliac segments were harvested after perfusion fixation with 10% neutral-buffered formalin.…”
Section: Histological Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies using coated stents that release rapamycin and paclitaxel have reported substantial decreases in the extent of in-stent restenosis during animal studies [8][9][10] and the initial phases of clinical trials. 11,12 However, coated stents could also be used to deliver genetic material to the cells of the vessel wall by diffusion from the polymer coating.…”
Section: Introductionmentioning
confidence: 99%